Charles Weissmann (1931–2025), an outstanding and captivating molecular biologist - Piet Borst; Richard A. Flavell (Proceedings of the National Academy of Sciences, 2026)
With the death of Charles Weissmann, molecular biology has lost of one of its most productive, outstanding, and critical representatives. A molecular biologist who became famous through his ground-breaking discoveries, as well as his scientific presentations, which always included “little stories,” used to illustrate the main points of his talks in a persuasive and amusing fashion. He will be remembered for unraveling the replication of RNA bacteriophages; for developing the first example of targeted mutagenesis, using viral RNA; for cloning the first interferon gene; for his decisive contributions to the origin and pathogenic effects of prions; and for the superb quality of his experimental work and mentorship.